The interplay of controlling the power exhaust and the tungsten content in ITER. (August 2017) - Dux, R.; Loarte, A.; Angioni, C.; Coster, D.; Fable, E.; Kallenbach, A.
Highlights: The main elements defining the tungsten content of ITER plasmas, i.e. gross erosion, prompt re-deposition and transport in the H-mode edge transport barrier are reviewed. ITER plasmas with divertor temperatures below 10 eV are predicted to have low tungsten content due to an acceptable low net W erosion yield and a favourable outward convection of W in the H-mode edge transport barrier of ITER. Contrary to our present day experience, edge localised modes are not essential to control the W content in ITER. Abstract: The main elements defining the tungsten content of an ITER plasma, i.e. the gross erosion, the prompt redeposition and the transport in the H-mode edge transport barrier are reviewed and it is investigated, whether the low tungsten concentration limit in the core calls for additional control of the divertor parameters or the ELM energy beyond the requirements set by the power handling capability of the divertor. The outcome is rather positive, since no further control seems to be required mainly because of the favourable transport in the H-mode edge transport barrier which provokes hollow tungsten profiles in the edge transport barrier for the expected pedestal parameters.